Vine-Canes Valorisation: Ultrasound-Assisted Extraction from Lab to Pilot Scale - Olena Dorosh; Manuela M. Moreira; Francisca Rodrigues; Andreia F. Peixoto; Cristina Freire; Simone Morais; Cristina Delerue-Matos (Molecules, 2020)
Wine production generates large amounts of vine-canes, a devalued by-product that could be used for the recovery of bioactive compounds. In this work, two vine-canes varieties, namely Touriga Nacional (TN) and Tinta Roriz (TR), were submitted to different ultrasound-assisted extraction (UAE) conditions. The highest phenolic and flavonoid content was observed for TR extract obtained at lab-scale without an ice bath and pilot-scale after 60 min of extraction (32.6 ± 2.1 and 26.0 ± 1.5 mg gallic acid equivalent/g dry weight (dw) and 9.5 ± 0.6 and 8.3 ± 0.8 mg epicatechin equivalents/g dw, respectively). Further, all extracts demonstrated a high antioxidant activity to scavenge DPPH free radicals with the best value reached by TR at the lab-scale without an ice bath after 30 min and pilot-scale extraction after 60 min (34.2 ± 2.4 and 33.4 ± 2.1 mg trolox equivalents/g dw, respectively). Extracts phenolic composition were also evaluated by HPLC, demonstrating that resveratrol, myricetin and catechin were the main compounds. According to our knowledge, this is the first time that a pilot scale of UAE of phenolic compounds from vine-canes was performed. This paper represents an important step to the use of UAE as an industrial process to recover bioactive compounds.